ON THE OCCURRENCE OF ANCHOVIELLA BAGANENSIS (HARDENBERG) AND A. BATAVIENSIS (HARBENBERG) ALONG THE SOUTH-EAST AND SOUTH-WEST COASTS OF INDIA - George, K C (Indian Journal of Fisheries, 2016)
Three Species of white-baits (Genus: Anchoviella) were described by Day (1878-89) from Indian waters under the generic name Engraulis Cuvier, 1817; viz., E. commersonianus (Lacepede, 1803), E. indicus (van Hasselt, 1823), and E. tri (Bleeker, 1852). Weber and de Beaufort (1913) recognised five species from the Indo-Australian archipelago, but used the generic name Stolephorus Lacepede, 1803. Important contributions to the knowledge of the systematics of these fishes have been made by Hardenberg (1933 and 1934) and by Fowler (1941). It was Fowler (1911) who emended Stolephorus Lacepede (strictly belonging to subfamily Dussumieriini, Clupeidas) and created the new genus Anchoviella (Engraulidae) with Engraulis perfasciatus Poey, orthotypic as the genotype.